Pre-competition weight loss among Polish taekwondo competitors - occurrence, methods and health consequences - Janiszewska, K.; Przybylowicz, K. E. (Archives of Budo, 2015)
Background and Study Aim: Negative health consequences of the rapid weight loss are a well-documented problem in combat sports such as wrestling and judo. The present study aimed the occurrence of pre-competition weight loss among polish taekwondo athletes, use of rapid weight loss methods and the evaluation of potential consequences of this process. Material and Methods: One hundred and twenty four participants were recruited and interviewed during national competition. Comparisons for age and training patterns between sexes were calculated using Mann-Whitney U test. The usage of rapid weight loss methods in sexes was compared with X?2 test. To compare occurrence of specific health symptoms the odds ratio calculation was used. Results: Seventy percent of the respondents declared weight loss before the competition. Food restriction, increased physical activity and exercising in impermeable clothes were cited as the most common methods used to achieve weight reduction. Athletes who were using rapid weight loss methods were almost 16 times more likely to develop feeling of reduced power/strength and increased irritability as well as 12 times more likely to feel fatigue before competition as compared to group of athletes non-using weight loss methods. Conclusions: Competitors who reduced their weight before competition were more likely to develop negative health consequences as athletes who didn`t follow weight reduction process. Preventive steps regarding pre-competition weight loss of taekwondo athletes should focus on changing behaviours from using rapid methods to using gradual methods of weight loss.